Scientometric study of drinking water treatments technologies: Present and future challenges. Issue 1 (1st January 2021) - Valdiviezo Gonzales, Lorgio G.; García Ávila, Fausto F.; Cabello Torres, Rita J.; Castañeda Olivera, Carlos A.; Alfaro Paredes, Emigdio A.
Abstract: The knowledge of the tendencies of the drinking water treatments was changing through the previous decades and it is necessary to improve it for the benefit of the human beings. In this sense, the purpose of the study was to develop a scientometric study about the drinking water treatments in the period 2010–2020 for providing the state of art of the studies about the drinking water treatments in diverse knowledge areas and new orientations for future research. For this purpose, a search of the information was performed both in the Web of Science (WoS) and Scopus databases, and all articles and reviews related to the field of water treatment or chemistry were included. The results showed that China, the USA and the Netherlands have the majority of the most cited publications and various related multidisciplinary topics, such as infrastructure, technologies and pollution. Therefore, the study allows concluding that there is a need for research on different technologies that contribute positively to obtaining quality water for consumption and for the use of routine activities, being the combination and integration of the different treatment processes a challenge for future studies.